A panchromatic study of stellar populations in Galactic Globular Clusters - Dalessandro, Emanuele <1981> (Alma Mater Studiorum - Università di Bologna, 2009)
The aim of this Thesis is to investigate (i) how common the bimodal Blue Straggler Stars (BSS) radial distribution is in stellar clusters and (ii) which are the physical processes that can produce this bimodality. We discuss possible relations between the properties of the BSS radial distribution and the dynamical state of the hosting clusters by making use of dynamical models and simulations. When relevant, we also discuss the possible links with some cluster "anomalies" and the effects of a massive object (like Imtermediate Mass Black Hole) in the cluster center. To this purpose we present the observational multiwavelength studies of the BSS populations and their radial distributions in 5 GGCs: M5, M55, M2, NGC 2419 and NGC 6388.